PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MENGGUNAKAN CANVA UNTUK GURU DI SMKN 2 PINGGIR - Yogi Yunefri; Sutejo; Yogi Ersan Fadrial (J-COSCIS : Journal of Computer Science Community Service, 2022)
SMK teachers as professional educators who act as facilitators in learning find innovations to find potential sources and learning media in the environment so that they can teach their students effectively. In order to become good facilitators, vocational school teachers are expected to be able to equip themselves with insight and skills in developing design and making learning media so that teachers can ensure good games. The reality shows that the teachers of SMKN 2 Pinggir in general have difficulty in improving the quality and effectiveness of learning at SMKN 2 Pinggir. This situation is due to the lack of buffer facilities and infrastructure that support the activity and enjoyment of students in learning and also because teachers do not yet have adequate insight and skills to make learning media that is fun for children. Therefore, the Service Team for the Faculty of Computer Science, University of Lancang Kuning provided Training on Making Learning Media Using Canva for Teachers at SMKN 2 Pinggir with the hope of increasing the effectiveness and quality of the learning process at SMKN 2 which will ultimately support the achievement of educational goals.